Authority, Participation, and Cultural Change in China; Essays by an European Study Group. Editado y con una introducción por Stuart R. Schram (Cambridge: Cambridge University Press, 1973). pp. VIII, 350. - K. Chang, Ming (Estudios de Asia y África, 1975)
-